Place of judiciary in separation of powers in Russia, CIS, European Union: a comparative legal analysis - N I Yaroshenko (RUDN Journal of Law, 2011)
The article is dedicated to the principle of division of powers and a special place of the judiciary. The study is based on an analysis of scientific works of Russian authors, the Constitution of Russia, CIS countries and the European Union, as well as the legal positions of the Constitutional Court of Russia.